Bycatch sea cucumber Holothuria scabra processing and the quality characteristics. Issue 1 (March 2020) - Aprianto, R; Amir, N; Kasmiati,; Matusalach,; Fahrul,; Syahrul,; Tresnati, J.; Tuwo, A
Abstract: Sea cucumbers are marine invertebrate animals that have high economic value. Indonesia is the main exporter of trepang over the world; however, this trepang export has not yet contributed to the improvement of community welfare. The low quality of trepang produced by Indonesia makes the economic value of trepang was still low. The low quality was caused by changes in processing stages due to decreasing the wild catch. Since the ban of the mini trawl use (cantrang), fishermen only process the bycatch sea cucumbers Holothuria scabra or sandfish. Trepang produce from sandfish is the most expensive one; the price can reach 3-5 million per kg. The study aims to analyze the quality and analyze the potential of developing the quality of trepang produce using sandfish. The decrease in sandfish catch volume after the Danish seine ban prohibits the stage changes in sandfish processing. Elimination of fumigation stage, the addition of storage in the refrigerator, addition of boiling, overcooking, and using excessive papaya leaves, were the main causes of less than the minimum value specified in SNI for appearance and odor characteristic. Although water, ash, protein, total plate count, Salmonella content, Lead, and Cadmium are in the decent range, the exporters still buy trepang at lower prices because exporters have to do reprocessing to improve the quality.